2020
DOI: 10.1111/jdv.16431
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of patients treated with apremilast in the real world: results from the APPRECIATE study

Abstract: BackgroundAPPRECIATE is a multinational, observational, retrospective, cross‐sectional study in patients treated for psoriasis with apremilast, an oral phosphodiesterase 4 inhibitor.ObjectivesTo describe the characteristics of patients with psoriasis treated with apremilast in the clinical setting, to evaluate real‐world outcomes of psoriasis treatment with apremilast and to better understand the perspectives of patients and physicians on treatment outcomes.MethodsIn six European countries, patients with chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
68
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(83 citation statements)
references
References 38 publications
13
68
2
Order By: Relevance
“…It should be noted that the effectiveness of therapy in this study was slightly lower than in international clinical trials and real-world studies [ 61 , 62 , 63 , 64 , 65 ]. So, 44% of patients did not reach PASI 50 by 14 weeks, and by 26 weeks—47%.…”
Section: Resultscontrasting
confidence: 68%
“…It should be noted that the effectiveness of therapy in this study was slightly lower than in international clinical trials and real-world studies [ 61 , 62 , 63 , 64 , 65 ]. So, 44% of patients did not reach PASI 50 by 14 weeks, and by 26 weeks—47%.…”
Section: Resultscontrasting
confidence: 68%
“…Patients with psoriasis often present with comorbid conditions and have a variety of detrimental characteristics (e.g., obesity, severity of disease, long duration of disease) that can negatively affect treatment outcomes [8]. Analysis of baseline characteristics related to treatment outcome was reported for psoriasis systemic treatments (oral and biologic) [2,3]. However, such data have not yet been produced for topical treatments as Cal/BD foam is the first drug receiving a label for longterm treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of patient characteristics on treatment outcome was studied in the moderate-to-severe patient population treated with systemic therapies (either orals or biologics). Thus far, long-term results from the use of topical therapies are lacking [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the mean dermatology life quality index (DLQI) score of the surveyed population decreased from 13.4 at initiation of treatment to 5.7 at 6 (1) months of treatment-a marked improvement in quality of life. 12 Other single-center and smaller study populations also have suggested increased realworld benefit. 13,14 Nonetheless, the rate and degree of clearance of plaques with apremilast seem to lag behind what is observed with many of the biologics and traditional medications employed to treat psoriasis.…”
Section: A B C F E Dmentioning
confidence: 99%